Staphylococcus caeli sp. nov., isolated from air sampling in an industrial rabbit holding. Issue 1 (14th November 2018) - MacFadyen, A. C.; Drigo, I.; Harrison, E. M.; Parkhill, J.; Holmes, M. A.; Paterson, G. K.
Abstract : Strain 82 T, a Gram-stain-positive, coagulase-negative staphylococcus was isolated from an air sample obtained from an industrial rabbit holding in Italy. It is phylogenetically closely related to the coagulase-negative species Staphylococcus saprophyticus, Staphylococcus xylosus and Staphylococcus edaphicus . However, it could be distinguished from these species by sequence differences between the 16S rRNA, hsp60, rpoB, dnaJ and gap genes. At the whole genome level, the isolate had an average nucleotide identity of <95 % and an inferred DNA–DNA hybridization of <70 % when compared to these species. Based on the genotypic results, it is proposed that this isolate is a novel species, with the name Staphylococcus caeli sp. nov. The type strain is 82B T (=NCTC 14063 T =CCUG 71912 T ).